1997
DOI: 10.1046/j.1464-410x.1997.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biodegradable self‐reinforced polyglycolic acid, poly‐dl‐lactic acid and stainless‐steel spiral stents on uroepithelium after Nd:YAG laser irradiation of the canine prostate

Abstract: Objective  To evaluate the safety and tissue effects on canine uroepithelium and prostate of biodegradable self‐reinforced polyglycolic acid (SR‐PGA) and self‐reinforced poly‐dl‐lactic acid (SR‐PLA) spiral stents compared to stainless‐steel (SS) spiral stents. Material and methods  Twenty‐five dogs (median body weight 12 kg) underwent a one‐stage midline laparotomy and cystotomy. A side‐firing Nd:YAG laser fibre was placed in the prostatic urethra antegradely and laser power applied at a setting of 20 W for 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…In an animal study Kemppainen et al [31] reported fewer encrustations on SR‐PLLA stents than on stainless steel stents in the anterior urethra of the rabbit. Likewise Petas et al [35,40] found some encrustation on gold‐plated steel wire (Prostakath®), but none on SR‐PGA or SR‐PLA 96/4 stents after incubation for 2 weeks in artificial urine. Recently a SR‐PLGA80/20 stent was shown to be markedly more resistant to encrustation than metallic urethral stents [41].…”
Section: Encrustationmentioning
confidence: 99%
“…In an animal study Kemppainen et al [31] reported fewer encrustations on SR‐PLLA stents than on stainless steel stents in the anterior urethra of the rabbit. Likewise Petas et al [35,40] found some encrustation on gold‐plated steel wire (Prostakath®), but none on SR‐PGA or SR‐PLA 96/4 stents after incubation for 2 weeks in artificial urine. Recently a SR‐PLGA80/20 stent was shown to be markedly more resistant to encrustation than metallic urethral stents [41].…”
Section: Encrustationmentioning
confidence: 99%
“…Zieren et al using a PGA mesh in combination with fibrin glue, found no infections after 90 days in a rat abdominal repair [40]. Petas et al compared stents made of PLA, PGA, and stainless-steel implanted in canine prostatic urethra after 10 seconds irradiation of the prostate side lobes with a 20 W CW Nd:YAG laser [41]. Examination of specimens after 1, 3, and 6 months showed a mild acute inflammation and foreign body reaction with the PLA and PGA stents that decreased over time.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, researchers have used biodegradable stents to treat benign prostatic hyperplasia. The results obtained yield more positive outcomes compared with those using suprapublic catheters (39)(40)(41)(42)(43). Selfreinforced poly(l-lactic acid) (PLLA) bioresorbable spiral stents are also undergoing evaluation for use in the anterior and posterior urethra and in the upper urinary tract for preventing urinary retention and for repairing local urethral trauma or defects (44,45).…”
Section: Stents In Urologymentioning
confidence: 99%